Funding eligibility requirements: inclusion, exclusion, and mediation in peace interventions. Issue 1 (2nd January 2021) - Ballesteros, Marie Donna M.
ABSTRACT: This article uses the case study of a network of NGOs involved in peace work in the Philippines to uncover the taken-for-granted reality of funding eligibility requirements – that they evade the question of who can strategically do peace work by defaulting to NGOs with the organisational structure to respond to donors' accountability requirements, and that these requirements shape the relationships of NGOs on the ground. Theoretically seen as the global imposition of technocracy on the local, this study expands on existing knowledge by capturing the dynamics in a blurred global-local demarcation and by showing agency, thereby refuting the narrative of a technocratic straitjacket.